FACE‐IT: A science gateway for food security research. (14th July 2015) - Montella, Raffaele; Kelly, David; Xiong, Wei; Brizius, Alison; Elliott, Joshua; Madduri, Ravi; Maheshwari, Ketan; Porter, Cheryl; Vilter, Peter; Wilde, Michael; Zhang, Meng; Foster, Ian
Summary: Progress in sustainability science is hindered by challenges in creating and managing complex data acquisition, processing, simulation, post‐processing, and intercomparison pipelines. To address these challenges, we developed the Framework to Advance Climate, Economic, and Impact Investigations with Information Technology (FACE‐IT) for crop and climate impact assessments. This integrated data processing and simulation framework enables data ingest from geospatial archives; data regridding, aggregation, and other processing prior to simulation; large‐scale climate impact simulations with agricultural and other models, leveraging high‐performance and cloud computing; and post‐processing to produce aggregated yields and ensemble variables needed for statistics, for model intercomparison, and to connect biophysical models to global and regional economic models. FACE‐IT leverages the capabilities of the Globus Galaxies platform to enable the capture of workflows and outputs in well‐defined, reusable, and comparable forms. We describe FACE‐IT and applications within the Agricultural Model Intercomparison and Improvement Project and the Center for Robust Decision‐making on Climate and Energy Policy. Copyright © 2015 John Wiley & Sons, Ltd.